Transcriptional Reprogramming of Arabidopsis thaliana Defence Pathways by the Entomopathogen Beauveria bassiana Correlates With Resistance Against a Fungal Pathogen but Not Against Insects - Raad, Maya; Glare, Travis R.; Brochero, Helena L.; Müller, Caroline; Rostás, Michael (Frontiers in Microbiology, 2019)
The entomopathogenic fungus Beauveria bassiana can adopt an endophytic lifestyle by colonising a wide array of plant species. Beauveria-colonised plants can show enhanced resistance against insects and plant pathogens alike. However, little is known about the molecular and physiological mechanisms that govern such interactions. Here, we assessed the effects of two B. bassiana strains (BG11, FRh2) on the growth of Arabidopsis thaliana and its resistance against two herbivore species and a phytopathogen. Plant responses were studied on the transcriptomic and metabolic level using microarrays and by measuring changes in defence-related phytohormones and glucosinolates. Root inoculation with B. bassiana BG11 significantly increased plant growth, while FRh2 had no such effect. Both Beauveria strains decreased leaf lesion area caused by the phytopathogen Sclerotinia sclerotiorum but did not affect population growth of the aphid Myzus persicae or the growth of Plutella xylostella caterpillars. Microarray analyses of leaves from endophyte-inoculated A. thaliana provided evidence for transcriptional reprogramming of plant defence pathways, with strain-specific changes in the expression of genes related to pathogenesis, phytoalexin, jasmonic (JA) and salicylic acid (SA) signalling pathways. However, B. bassiana colonisation did not result in higher concentrations of JA and SA or major changes in leaf glucosinolate (GLS) profiles. We conclude that the endophyte B. bassiana induces plant defence responses and hypothesise that these contribute to enhanced resistance against S. sclerotiorum.